Effectiveness of Digital Marketing Strategy Through Social Media on Sales of UD. Purnama Jati Center For Special Jember Souvenirs - Siti Isnaini (West Science Journal Economic and Entrepreneurship, 2025)
Jember Regency, East Java, with an area of ​​around 3,306.69 km², is famous not only for its agricultural and tourism sectors, but also as a center for typical regional souvenirs such as suwar-suwir, prol tape, edamame, Jember coffee, and typical Jember chocolate. The existence of various souvenir shops on the main route, city center and tourist locations contributes to the tourism industry and strengthens Jember's identity as a producer of local products that are sought after by tourists. This research aims to find out whether the use of social media Whatsapp, Instagram, Facebook and Tiktok has a significant impact on increasing UD sales. Purma Jati Jember souvenir center. The method used in this research is a descriptive method with a quantitative convirmatory approach. The population of this research is customers from UD. Purnama Jati and followers of UD's social media accounts. Purnama Jati who follows social media Whatsapp, Instagram, Facebook and Tiktok. The sampling method used purposive sampling, the sample was 105 respondents. The results of this research are that marketing strategies via WhatsApp have proven to be effective with an effectiveness level of 84%, Instagram at 85%, Facebook at 77% and Tiktok at 86%. The results of the effectiveness level of social media Whatsapp, Instagram and Tiktok can be said to be "Very Good" and social media Facebook can be said to be "Good".